BUDAYA ORGANISASI, KEPEMIMPINAN, DAN KOMPETENSI KONTRIBUSINYA TERHADAP KINERJA PETUGAS LAPANGAN KB (Study kasus di DP2KBP3A Kabupaten Subang) - Endang Dermawan; Ani Yunaningsih (Scientia Regendi, 2021)
This research focuses on organizational culture, leadership, competence, and performance. The sample of this study was a KB fieldworker with the status of a civil servant in the Population Control Department for Family Planning for Women's Empowerment for Child Protection in Subang Regency. To find out between variables, the analysis used is Path Analysis. This study concludes that organizational culture influences positively insignificant performance. Leadership has a significant effect on performance. Competence has a significant effect on performance. And on average there is an influence of organizational culture, leadership, and competence on performance. Keywords: Organizational Culture, Leadership, Competence, Performance, KB Field Staff DP2KBP3A.